2009
DOI: 10.3928/02793695-20091103-96
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Animal-Assisted Activity on Inpatients with Schizophrenia

Abstract: The aim of this study was to evaluate the effects of animal-assisted activity on self-esteem, control over activities of daily living, and other psycho-physiological aspects among Taiwanese inpatients with schizophrenia. Thirty participants were randomly assigned to either the treatment or control group. A weekly animal-assisted activity program was arranged for patients in the treatment group for 2 months. A questionnaire assessing self-esteem, self-determination, social support, and psychiatric symptoms was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 27 publications
2
42
1
5
Order By: Relevance
“…Chu et al (2009) demonstrated improvement in self-esteem and self-determination and a decrease in schizophrenic symptoms among 30 schizophrenic patients in an 8-month intervention with a therapy dog compared with treatment without a dog. Correspondingly, Berget et al (2008) found significantly increased self-efficacy, measured with the Generalized SelfEfficacy Scale (Schwarzer, 1993), among a heterogenic population of persons with psychiatric disorders during a 3-month intervention (3 hours, twice a week) with traditional farm animals.…”
Section: Effectiveness and Measurement Of Animal-assisted Interventionsmentioning
confidence: 97%
“…Chu et al (2009) demonstrated improvement in self-esteem and self-determination and a decrease in schizophrenic symptoms among 30 schizophrenic patients in an 8-month intervention with a therapy dog compared with treatment without a dog. Correspondingly, Berget et al (2008) found significantly increased self-efficacy, measured with the Generalized SelfEfficacy Scale (Schwarzer, 1993), among a heterogenic population of persons with psychiatric disorders during a 3-month intervention (3 hours, twice a week) with traditional farm animals.…”
Section: Effectiveness and Measurement Of Animal-assisted Interventionsmentioning
confidence: 97%
“…Terms & Conditions of access and use can be found at http://www.tandfonline.com/page/terms-and-conditions two types of intervention: "animal-assisted therapy" (aat), a goal-directed intervention in which an animal is an integral part of a treatment process to achieve specific goals, and "animal-assisted activities" (aaa), a less structured intervention which aims to achieve positive psychological outcomes through creating a positive environment with animals (Delta Society n.d.). although aaIs have incorporated a wide range of animals (e.g., Breitenbach et al 2009), the most common programs have focused on horses (trotter et al 2008;Burgon 2011), farm animals (e.g., Pedersen et al 2012), or domestic pets (e.g., Chu et al 2009). there is generally agreement that aaIs lead to positive psychological outcomes (e.g., Nimer and lundahl 2007;Wells 2009;Ernst 2012).…”
Section: A Systematic Review Of Randomized Controlled Trials Of Animamentioning
confidence: 99%
“…There was a significant decrease in depression and an increase in arterial oxygen in the experimental group but there were similar decreases in anxiety, hostility, and blood pressure in both the experimental and control groups. Chu et al (2009) conducted a randomized pre-post between subjects study with the additional validity check of raters blind to condition. Their subjects were adults with schizophrenia.…”
Section: Specific Studiesmentioning
confidence: 99%